Acetylcholinesterase activity and oxidative stress indices in cerebellum, cortex and hippocampus of rats exposed to lead and manganese - Afolabi, Olusegun; Sulaiman, Oladele; Adeleke, Gbadedo; Wusu, Dorcas (International Journal of Biological Research, 2016)
Human exposure to metals is a major health concern in the world as a result of increased industrialization. The present study was designed to investigate the toxic effect of lead and manganese alone and in combination on different regions of rat brain, namely cerebellum, cortex and hippocampus. Adult male Wistar rats were exposed to 100 ppm lead as lead acetate, 100 ppm manganese as manganese chloride, and lead and manganese in combination in their drinking water for 4 weeks. Following either lead or manganese exposure, acetylcholinesterase activity and the antioxidant enzymes, superoxide dismutase and catalase activities were inhibited. Likewise, malonylaldehyde level, a marker of lipid peroxidation and protein carbonyl groups used to assess oxidatively modified proteins were markedly increased by exposure to either metals. The non-enzymatic antioxidants, reduced glutathione and total thiol groups were significantly (p < 0.05) depleted by these metals. However, these aspects were more pronounced in animals exposed to the mixture of both lead and manganese. The metals displayed additive, as well as, potentiation effect in their interactions in the brain regions. It can thus, be concluded that the mixture of lead and manganese demonstrated a higher neurotoxic effects than does either metals alone.